Comparison of mouthpart morphology of three species of Mexican Oniticellini (Coleoptera: Scarabaeidae: Scarabaeinae) in relation to their trophic habits - Irma López Guerrero (The Coleopterists Bulletin, 2011)
The purpose of this study is to describe the differences in the mouthparts of three Mexican species of Oniticellini that make use of different trophic resources. Euoniticellus intermedius (Reiche) is a coprophage par excellence, Attavicinus monstrosus (Bates) is a specialist in dry particles, and Liatongus rhinocerulus (Bates), a saprophage, is sometimes observed in excrement and on small cadavers, but mainly on rotting mushrooms. The results show no substantial structural differences among the species studied, though for each one, particular characteristics are evident.